Effect of Variant Manure on Generation Time in Daphnia sp. - Herman Hamdani; Asep Sahidin; Taufiq Hidayat (Journal Omni-Akuatika)
The research about generation times of Daphnia sp. was carried out on Mei – June 2017 in Biology Laboratory, FPIK UNPAD. The objective of this research was to analyse the generation time of Daphnia sp. in different manure. The research used experimental  method Randomized Completely Block Design (RCBD) with four treatment and three replication. The variant of manure as treatment were chicken manure (A), quail manure (B), cow manure (C), and goat manure (D). The weight for each manure media as many as  2,4 g/l in 1 litre of glass media. The best performance of life table distribution showed from the cow manure, but quail manure treatment give the best of all biological factor, it mean that Daphnias were cultured with quail manure have good performance in biological parameter.